Perancangan Photobook Penjahit Taruna Menggunakan Teknik Photostory - Zaenal Mustofa; Jozua F Palandi; Ahmad Zakiy Ramadhan (LPPM STIKI Malang, 2021)
The design of the cadets tailor photobook was made based on Muhammad Hasan's experience in his struggle to participate in the army selection but the results did not match what he had dreamed of since he was a child, but he did not give up there and decided to become an army dress tailor because he felt he was working as an army tailor is still closely related to what he aspires to. Based on this explanation, a cadet tailor photobook was designed with the aim of inspiring prospective army registrants who would take part in the army selection and also as encouragement in undergoing the test stages in the army registration selection. The methodology used in this design uses Drs. Sadjiman Ebdi Sanyoto which has been tailored to the needs of designing a cadet tailor photobook. The results of this design are photobooks as the main media and supporting media in the form of posters, xbanners, pins and also tote bags.